2021
DOI: 10.3390/membranes11040241
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Effects of Titanium Dioxide (TiO2) and Polyvinyl Alcohol (PVA) in the Separation and Antifouling Performance of Thin-Film Composite Polyvinylidene Fluoride (PVDF) Membrane

Abstract: In this study, thin-film composite (TFC) polyvinylidene fluoride (PVDF) membranes were synthesized by coating with titanium dioxide (TiO2)/polyvinyl alcohol (PVA) solution by a dip coating method and cross-linked with glutaraldehyde. Glutaraldehyde (GA) acted as a cross-linking agent to improve the thermal and chemical stability of the thin film coating. The incorporation of TiO2 in the film enhanced the hydrophilicity of the membrane and the rejection of dyes during filtration. The layer of TiO2 nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In photocatalytic membranes, nanoscale inorganic/organic photocatalysts are embedded in a membrane matrix to improve the properties of the resulting polymer [82,[105][106][107]. Hamed et al [108] eluded that TiO 2 nanoparticles can coordinate with the surface of the polymer membrane and Ti +4 makes ion connections with oxygen atoms of carboxylic groups of polymers or by making H-bonding with carbonyl or hydroxyl groups on the TiO 2 surface.…”
Section: Tio 2 Nanoparticle-coated Polymer Membranesmentioning
confidence: 99%
See 4 more Smart Citations
“…In photocatalytic membranes, nanoscale inorganic/organic photocatalysts are embedded in a membrane matrix to improve the properties of the resulting polymer [82,[105][106][107]. Hamed et al [108] eluded that TiO 2 nanoparticles can coordinate with the surface of the polymer membrane and Ti +4 makes ion connections with oxygen atoms of carboxylic groups of polymers or by making H-bonding with carbonyl or hydroxyl groups on the TiO 2 surface.…”
Section: Tio 2 Nanoparticle-coated Polymer Membranesmentioning
confidence: 99%
“…When the membranes were modified with diethanolamine (DEA), Hamed et al [108] found that a high concentration of TiO 2 coated on the polyvinylidene fluoride (PVDF) membrane improved pure water flux. Although embedding nanoparticles onto membranes remove unwanted nanoparticles after treatment, the polymer phase material covering the nanoparticles can reduce the active usable surface area [107]. Owing to the blockage of the membrane pores by TiO 2 nanoparticles, the photocatalytic membrane's pure water flux usually decreases as the concentration of TiO 2 in the coating phase rises [58,107,109,111].…”
Section: Tio 2 Nanoparticle-coated Polymer Membranesmentioning
confidence: 99%
See 3 more Smart Citations